The impact of an alcohol harm reduction intervention on interpersonal violence and engagement in sex work among female sex workers in Mombasa, Kenya: Results from a randomized controlled trial. (1st April 2016) - Parcesepe, Angela M.; L′Engle, Kelly L.; Martin, Sandra L.; Green, Sherri; Sinkele, William; Suchindran, Chirayath; Speizer, Ilene S.; Mwarogo, Peter; Kingola, Nzioki
Highlights: This study evaluated to what extent an alcohol reduction intervention was associated with reduced violence or engagement in sex work among FSWs. The intervention was associated with significant decreases in having been robbed or not paid by a client immediately post-intervention. The intervention was associated with decreased verbal abuse from paying partners immediately and 6 months post-intervention. Those assigned to the alcohol intervention had significantly lower odds of engaging in sex work immediately and 6 months post-intervention. Findings demonstrate potential for brief alcohol reduction interventions to positively influence the health and safety of female sex workers. Abstract: Aims: To evaluate whether an alcohol harm reduction intervention was associated with reduced interpersonal violence or engagement in sex work among female sex workers (FSWs) in Mombasa, Kenya. Design: Randomized controlled trial. Setting: HIV prevention drop-in centers in Mombasa, Kenya. Participants: 818 women 18 or older in Mombasa who visited HIV prevention drop-in centers, were moderate-risk drinkers and engaged in transactional sex in past six months (410 and 408 in intervention and control arms, respectively). Intervention: 6 session alcohol harm reduction intervention. Comparator: 6 session non-alcohol related nutrition intervention. Measurements: In-person interviews were conducted at enrollment, immediately post-intervention and 6-months post-intervention. General linear mixed models examined associations between intervention assignment and recent violence (physical violence, verbal abuse, and being robbed in the past 30 days) from paying and non-paying sex partners and engagement in sex work in the past 30 days. Findings: The alcohol intervention was associated with statistically significant decreases in physical violence from paying partners at 6 months post-intervention and verbal abuse from paying partners immediately post-intervention and 6-months post-intervention. Those assigned to the alcohol intervention had significantly reduced odds of engaging in sex work immediately post-intervention and 6-months post-intervention. Conclusions: The alcohol intervention was associated with reductions in some forms of violence and with reductions in engagement in sex work among FSWs in Mombasa, Kenya.